Diode laser for excisional biopsy of a peripheral ossifying fibroma: A case report - Vlachos Emmanouil; Gkouzoula Despina; Fourmousis Ioannis (Journal of Dental Problems and Solutions - Peertechz Publications, 2020)
Peripheral Ossifying Fibroma is one of the most common reactive lesions of connective tissue located on gingivae. It appears as a well-defined, benign, fibrous overgrowth and is associated with chronic trauma or irritation. It can be pedunculated or sessile, usually covered by smooth normal epithelium and it can sometimes appear ulcerated as a result of mechanical trauma.  Conventional treatment of Peripheral Ossifying Fibroma includes excision of lesion down the level of periodontal ligament and periosteum. Another contemporary modality of excising oral soft-tissue lesions are dental lasers. They have been widely accepted and increasingly used in daily practice. More specifically, in oral soft tissue surgery, lasers minimize operative and postoperative bleeding, swelling and scarring, and are easy to handle. Moreover, lasers do not alter the microarchitecture of the biopsy specimen and are well accepted by the patients.  In this case report, we present a 30-year old man diagnosed with a recurrent peripheral ossifying fibroma in the mandibular incisors' region. The patient was firstly diagnosed with peripheral ossifying fibroma at the age of 18 and had a few recurrence episodes after excision of the lesion with traditional surgical treatment. This oral lesion was excised by using diode laser (980nm), and the specimen was sent for histopathological analysis. In this case report we describe advantages and superiority of diode laser application in excision of Peripheral Ossifying Fibroma. In general, diode laser may be an alternative reliable and effective treatment option for excision of oral soft-tissue lesions.